UPAYA DINAS KOPERASI, USAHA MIKRO, DAN PERDAGANGAN (DISKUMDAG) KOTA BATU DALAM MEMBERDAYAKAN PELAKU USAHA KECIL MENENGAH (UKM) PRODUK TUJUAN EKSPORT - Ruth Agnesia Sembiring; Tia Subekti; Mitha Mawar Nia Bella (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2020)
Abstract Small and Medium Enterprises are an important pillar in supporting the economy of the middle to lower class communities. Every region in Indonesia has SMEs but only a few are able to have export quality. Local products that are presented in the form of SMEs are often unable to compete with products from large-scale industries or even unable to compete with imported products. This is a threat to the economic continuity of the middle to lower class communities considering that today's global market opportunities are difficult to stem the flow of imports from other countries. One of the efforts that can be used to maintain SMEs is to improve the quality of SMEs with export standards. Batu City has 365 UKMs spread over 3 districts. This condition shows how UKM has become the economic support for the people of Batu. This research looks at